Tecnología digital y resolución de problemas - De Faria Campos, Edison (2008)
It refers to the use of digital technologies for problem solving in the programs of mathematics of the Costa Rica Ministry of Education and some theories related to the subject are described, particularly that of instrumental mediation and of executable systems of representation.